2021
DOI: 10.3390/molecules26040858
|View full text |Cite
|
Sign up to set email alerts
|

Stevioside Activates AMPK to Suppress Inflammation in Macrophages and Protects Mice from LPS-Induced Lethal Shock

Abstract: Stevioside, a diterpenoid glycoside, is widely used as a natural sweetener; meanwhile, it has been proven to possess various pharmacological properties as well. However, until now there were no comprehensive evaluations focused on the anti-inflammatory activity of stevioside. Thus, the anti-inflammatory activities of stevioside, both in macrophages (RAW 264.7 cells, THP-1 cells, and mouse peritoneal macrophages) and in mice, were extensively investigated for the potential application of stevioside as a novel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…It has been widely confirmed that AMPK/NF-κB pathway regulates inflammatory response and induces iNOS transcription in sepsis [ 21 , 27 ]. Inflammatory cytokines could down-regulate the expression of α1-adrenergic receptors.…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely confirmed that AMPK/NF-κB pathway regulates inflammatory response and induces iNOS transcription in sepsis [ 21 , 27 ]. Inflammatory cytokines could down-regulate the expression of α1-adrenergic receptors.…”
Section: Resultsmentioning
confidence: 99%
“…43 In addition, as an important signal transduction and regulatory factor in the TGF-β family, HIF-1α can promote the production of RAW cell inflammatory factors under the mediation of NFκB. 44 Overall, the expression of pro-inflammatory-related genes can be significantly controlled under GL hydrogel treatment.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…However, recent studies have shown that acute and uncontrolled chronic inflammation is associated with multiple diseases, including rheumatoid arthritis, metabolic syndrome, inflammatory bowel disease, diabetes, and various types of cancer (Ahn et al, 2018;Xu et al, 2021a, b). Growing prevalence of these inflammatory-related diseases means they are now among the leading causes of morbidity worldwide (Hsieh et al, 2021;Wei et al, 2021). Therefore, finding effective and low-toxicity anti-inflammatory drugs to control inflammation is critical for the prevention or treatment of these diseases (Tang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%